Taxonomy of the fresh-water algae of Laguna de Bay and vicinity. - Pantastico, Julia B. (Tagig, Metro Manila, Philippines National Research Council of the Philippines, 1977)
Bulletin / National Research Council of the Philippines ; no. 61
Keywords: Freshwater algae -- Philippines